2005
DOI: 10.1002/ejoc.200400727
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Reaction of Lawesson’s Reagent with N‐Alkylhydroxamic Acids

Abstract: The mechanism of the reaction under discussion has been established by investigating the products of the reaction between 2,4‐bis(4‐methoxyphenyl)‐1,3,2,4‐dithiadiphosphetane 2,4‐disulfide (Lawesson’s reagent, LR) and N‐alkylhydroxamic acids HAs 1. The primary intermediate is an adduct, O‐dithiophosphonylated hydroxamic acid 19, which decomposes to yield metathiophosphonate (AnsPOS), a sulfur atom, and an amide. At the same time, owing to the co‐existence of 19 and metadithiophosphonate (AnsPSS) in equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Amides are better nucleophiles and therefore react with LR much faster than esters, but the effect of substituents on the thionation rate of amides has never been studied [10]. In the previous report [8], it was found that EWG-substituted HAs give better yields of the corresponding THAs 2. It can be assumed that this effect results from both lower nucleophilicity and stronger N O bond of EWG-substituted HAs as compared with EDG-substituted ones.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Amides are better nucleophiles and therefore react with LR much faster than esters, but the effect of substituents on the thionation rate of amides has never been studied [10]. In the previous report [8], it was found that EWG-substituted HAs give better yields of the corresponding THAs 2. It can be assumed that this effect results from both lower nucleophilicity and stronger N O bond of EWG-substituted HAs as compared with EDG-substituted ones.…”
Section: Methodsmentioning
confidence: 98%
“…NMethyl-, N-tert-butyl-and N-benzylhydroxylamine hydrochlorides were obtained from Aldrich. Hydroxamic acids 1Aa [14], 1Ab [15], 1Ac [16], 1Ad [17], 1Ae-1Af [18], 1Aj-1Ak [19], 1Al [20], 1Am [21], 1An [22], 1Ba [23], 1Bb-1Bc [24], 1Bd [25], 1Be [26], 1Bf [8], 1Bh [8], 1Bk [7], 1Bo [8], and 1Bu [27] are known compounds and were synthesized according to general procedure described below. Thiohydroxamic acids 2Bh, 2Bi, 2Bm, 2Bo, and 2Bp were prepared and characterized previously [11].…”
Section: Experimental General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct thionation of hydroxamic acids with Lawesson´s reagent (LR) 142 can be very useful in the synthesis of thio analogues of natural hydroxamates and N-hydroxythiopeptides. 55 …”
Section: Scheme 49mentioning
confidence: 99%
“…Only one patent deals with the preparation of N-methyl-N-diethoxyphosphinthioyloxy acetamide starting from N-chloro-N-methylacetamide in moderate yield [10]. Recently, we isolated N-isopropyl-N-[methoxy) (4-methoxyphenyl)phosphinothioyloxy]benzamide from the reaction mixture of the corresponding hydroxamic acid and Lawesson's reagent (LR) [11].…”
Section: Introductionmentioning
confidence: 99%